Hemodinamik Pasien Akut Miokard Infark (AMI) Di Ruang Perawatan Kritis - Widiyaningsih, Widiyaningsih; Kusyati, Eni (Journal of Holistic Nursing Science, 2019)
Acute myocardial infarction (AMI) is a major cardiovascular problem because it causes high rates of hospital care and mortality due to complications that can occur in AMI is cardiac arrest. Objective to describe noninvasive hemodynamic of acute myocardial infarction (AMI) patients in ICU. This type of research used descriptive quantitative research with retrospective design. The sample of study was 52 respondents. The sampling technique in this study used total sampling. The research was done from May 2017 until July 2018. 52 respondents have had the average systolic was 113.96 mmHg, on average Diastolic 73.21 mmHg, average MAP was 86.76 mmHg, average heart rate 116,21 bpm, average oxygen saturation 92,08%, and lethal ECG were 80.8%.Average systolic, diastolic blood pressure, and MAP was normal, the average of heart rate had increased than normal, average oxygen saturation less than 92%, and almost respondents have lethal ECG. Hemodynamic monitoring for AMI patient very important to access the prognosis of patient condition.